Chronic Kidney Disease Risk in African and Caribbean Populations With HIV. (6th July 2018) - Jose, Sophie; Hamzah, Lisa; Jones, Rachael; Williams, Debbie; Winston, Alan; Burns, Fiona; Phillips, Andrew N; Sabin, Caroline A; Post, Frank A; ,
Abstract : People of West-African heritage were noted to be at 6-fold greater risk of end-stage kidney disease compared to those originating from East Africa, which suggests that genetic factors are likely determinants of kidney disease in these populations. Abstract: We conducted an observational cohort study of end-stage kidney disease (ESKD) in >7000 African and Caribbean people with HIV in the UK. Using Poisson regression and East Africans as the reference group, the adjusted incidence rate ratio (95% confidence interval) of ESKD was 3.14 (1.26–7.84) in Southern Africans, 6.35 (2.53–15.96) in West Africans, and 5.26 (1.91–14.43) in Caribbeans. Higher CD4 cell count and suppressed HIV replication were associated with reduced risk of ESKD. The risk of ESKD varied among HIV-positive people of African heritage, with the highest rates observed in those of West African descent.